5 a) Tìm n nguyên dương để n5 + 1\(⋮\)n3 + 1
b) Tìm n e Z để n5 + 1\(⋮\)n3 +1
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\Leftrightarrow n^5+n^2-n^2+1⋮n^3+1\)
\(\Leftrightarrow-n^3+n⋮n^3+1\)
\(\Leftrightarrow n=1\)
\(\Leftrightarrow n^3+n^2-n^2-n-2n-2+6⋮n+1\)
\(\Leftrightarrow n+1\in\left\{1;-1;2;-2;3;-3;6;-6\right\}\)
hay \(n\in\left\{0;-2;1;-3;2;-4;5;-7\right\}\)
\(a,n^3-2n^2+3n+3=n^3-n^2-n^2+n+2n-2+5\\ =\left(n-1\right)\left(n^2-n+2\right)+5\\ \Leftrightarrow n^3-2n^2+3n+3⋮\left(n-1\right)\\ \Leftrightarrow5⋮n-1\\ \Leftrightarrow n-1\in\left\{-5;-1;1;5\right\}\\ \Leftrightarrow n\in\left\{-4;0;2;6\right\}\)
\(b,\Leftrightarrow x^4+6x^3+7x^2-6x+a\\ =x^4+3x^3-x^2+3x^3+9x^2-3x-x^2-3x+1-1+a\\ =\left(x^2+3x-1\right)\left(x^2+3x-1\right)-1+a\\ =\left(x^2+3x-1\right)^2+a-1\)
Để \(x^4+6x^3+7x^2-6x+a⋮x^2+3x-1\)
\(\Leftrightarrow a-1=0\Leftrightarrow a=1\)
\(2,\\ n=0\Leftrightarrow A=1\left(loại\right)\\ n=1\Leftrightarrow A=3\left(nhận\right)\\ n>1\Leftrightarrow A=n^{2012}-n^2+n^{2002}-n+n^2+n+1\\ \Leftrightarrow A=n^2\left[\left(n^3\right)^{670}-1\right]+n\left[\left(n^3\right)^{667}-1\right]+\left(n^2+n+1\right)\)
Ta có \(\left(n^3\right)^{670}-1⋮\left(n^3-1\right)=\left(n-1\right)\left(n^2+n+1\right)⋮\left(n^2+n+1\right)\)
Tương tự \(\left(n^3\right)^{667}⋮\left(n^2+n+1\right)\)
\(\Leftrightarrow A⋮\left(n^2+n+1\right);A>1\)
Vậy A là hợp số với \(n>1\)
Vậy \(n=1\)
\(3,\)
Đặt \(A=n^4+n^3+1\)
\(n=1\Leftrightarrow A=3\left(loại\right)\\ n\ge2\Leftrightarrow\left(2n^2+n-1\right)^2\le4A\le\left(2n^2+n\right)^2\\ \Leftrightarrow4A=\left(2n^2+n\right)^2\\ \Leftrightarrow4n^2+4n^3+4=4n^2+4n^3+n^2\\ \Leftrightarrow n^2=4\Leftrightarrow n=2\)
Vậy \(n=2\)